2012
DOI: 10.1007/s00701-012-1502-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying pseudoneoplasms of the neuraxis (CAPNON): clinical features and therapeutic options

Abstract: Calcifying pseudoneoplasms are rare benign lesions of the CNS of yet unknown origin. Because of the increasing number of reports, this clinical entity should be taken into consideration in the differential diagnosis of intracranial and intraspinal calcified lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 18 publications
2
50
0
2
Order By: Relevance
“…The frequent adjacent granulomatous and inflammatory reaction along with an indolent course and a generally good prognosis support a benign or reactive rather than neoplastic process . Of the 65 cases of CAPNON that we identified in the literature, only one case presented with two separate lesions diagnosed 8 years apart in the same individual . The remaining 64 cases were solitary.…”
Section: Introductionmentioning
confidence: 77%
“…The frequent adjacent granulomatous and inflammatory reaction along with an indolent course and a generally good prognosis support a benign or reactive rather than neoplastic process . Of the 65 cases of CAPNON that we identified in the literature, only one case presented with two separate lesions diagnosed 8 years apart in the same individual . The remaining 64 cases were solitary.…”
Section: Introductionmentioning
confidence: 77%
“…Resection has been proposed as the most appropriate treatment for CAPNON. 3 However, large lesions as in our case may not be amenable to complete resection. Owing to the lack of larger series, the value of complete vs partial resection remains speculative.…”
Section: Sectionmentioning
confidence: 62%
“…It has been described in patients aged from 6 to 68 years with a preponderance of males. 3 The clinical symptoms and signs vary and depend on the localization of the mass, with seizures as the most frequent symptom if the lesion is located intracranially.…”
Section: Sectionmentioning
confidence: 99%
“…[49] CT studies showed that these lesions are a hyperdense lesion while MR studies demonstrated hypointense T1- and T2-weighted images with limited edema and contrast enhancement. [1] Differential diagnoses include meningioma, granulomatous lesions, astrocytoma with calcification, oligodendrogliomas, and hamartomas.…”
Section: Discussionmentioning
confidence: 99%